Representation of Instantaneous and Short-Term Loudness in the Human Cortex - Thwaites, Andrew; Glasberg, Brian R.; Nimmo-Smith, Ian; Marslen-Wilson, William D.; Moore, Brian C. J. (Frontiers in Neuroscience, 2016)
Acoustic signals pass through numerous transforms in the auditory system before perceptual attributes such as loudness and pitch are derived. However, relatively little is known as to exactly when these transformations happen, and where, cortically or sub-cortically, they occur. In an effort to examine this, we investigated the latencies and locations of cortical entrainment to two transforms predicted by a model of loudness perception for time-varying sounds: the transforms were instantaneous loudness and short-term loudness, where the latter is hypothesized to be derived from the former and therefore should occur later in time. Entrainment of cortical activity was estimated by electro- and magneto-encephalographic (EMEG) activity, recorded while healthy subjects listened to continuous speech. There was entrainment to instantaneous loudness bilaterally at 45 ms, 100 ms and 165 ms, in Heschl’s gyrus, dorsal lateral sulcus and Heschl’s gyrus respectively. Entrainment to short-term loudness was found in both the dorsal lateral sulcus and superior temporal sulcus at 275 ms. These results suggest that short-term loudness is derived from instantaneous loudness, and that this derivation occurs after processing in sub-cortical structures.